Corrigendum to ‘Guanine condensates as covalent materials and the concept of cryptopores’ [Carbon 172 (2021) 497–505] (Carbon (2021) 172 (497–505), (S0008622320310113), (10.1016/j.carbon.2020.10.047)) - Kossmann, Janina; Piankova, Diana; Tarakina, Nadezda; Heske, Julian; Kühne, Thomas D.; Schmidt, Johannes; Antonietti, Markus; Lopez-Salas, Nieves (Carbon, 2021)
The authors regret that the heat of adsorption values written in the text (45 and 67 kJ/mol for cG@600 and cG@700, respectively) and given in the Table S1 and Figure S9 (of 51 and 59 kJ/mol for cG@600 and cG@700, respectively) do not match. The correct data are those found in the supporting information (i.e. Figure S9 and Table S1). The values were changed after collecting the isotherms with more data points. There are only two fragments to correct in the text, which are: “Furthermore, the calculated heat of adsorption at low relative pressures of samples cG@600 and cG@700 is of 45 kJ mol−1 and 67 kJ mol−1, respectively” (p.501). To: “Furthermore, the calculated heat of adsorption at low relative pressures of samples cG@600 and cG@700 is of 51 kJ mol−1 and 59 kJ mol−1, respectively” (p.501) And. “This finding, together with the CO2 heat of adsorption values of up to 67 kJ mol−1, indicates that this process is closer to a highly selective chemisorption rather than simple physisorption but still reversible under practical conditions.” (p.503). To: “This finding, together with the CO2 heat of adsorption values of up to 59 kJ mol−1, indicates that this process is closer to a highly selective chemisorption rather than simple physisorption but still reversible under practical conditions.” (p.503). We are very sorry for this sloppy mistake and we would like to apologise for any inconvenience caused.
CRIS-Team Scopus Importer:2023-03-20